2022
DOI: 10.1101/2022.03.09.483635
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nucleocapsid-specific humoral responses improve the control of SARS-CoV-2

Abstract: SummaryThe spike protein of SARS-CoV-2 is a critical antigen present in all approved SARS-CoV-2 vaccines. This surface viral protein is also the target for all monoclonal antibody therapies, but it is unclear whether antibodies targeting other viral proteins can also improve protection against COVID-19. Here, we interrogate whether nucleocapsid-specific antibodies can improve protection against SARS-CoV-2. We first immunized mice with a nucleocapsid-based vaccine, and then transferred sera from these mice into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Dangi et al, 2021, also evidenced that combining spike and nucleocapsid vaccine formulations improve distal protection in brain (Dangi et al, 2021). These authors even demonstrated the protective role of anti-N Abs, proven by passive transfer experiments (Dangi et al, 2022).…”
Section: Discussionmentioning
confidence: 95%
“…Dangi et al, 2021, also evidenced that combining spike and nucleocapsid vaccine formulations improve distal protection in brain (Dangi et al, 2021). These authors even demonstrated the protective role of anti-N Abs, proven by passive transfer experiments (Dangi et al, 2022).…”
Section: Discussionmentioning
confidence: 95%
“…Most antigenic sites where variants capable of immune evasion emerge are enriched in IDRs [ 2 , 219 ] and can compromise effectiveness of neutralizing antibodies generated by vaccines [ 220 ]. Approximately 51% of experimentally determined IDRs in SARS-CoV-2 are located in the N protein [ 2 ], and not surprisingly, sera from mice immunized with nucleocapsid-based vaccines may enhance control of SARS-CoV-2 infections [ 221 ]. Even though human coronaviruses are not distinguished for possessing abundant IDRs—~7.3% in the NL63 proteome compared to 77.3% in that of the Avian carcinoma virus [ 202 ]—and the SARS-CoV-2 proteome exhibits an extremely high level of structural order with only a few functionally relevant proteins displaying IDRs [ 217 ], an extensive examination of the dark proteome of this virus revealed that almost the entire SARS-CoV-2 virus contain molecular recognition features that are important sites for intrinsic disorder-based protein–protein interactions [ 222 ].…”
Section: Sars-cov-2 Proteins Phase Separation Disrupt Host Biomolecul...mentioning
confidence: 99%
“…In addition, vaccine-induced N-specific immune responses have been associated with S-independent protective immunity in animal models (Afkhami et al, 2022;Dangi et al, 2021;Matchett et al, 2021). Recent studies have also shown that N-specific non-NAb promotes antibody-dependent cellular cytotoxicity and other Fcreceptor-mediated functions and can result in the control of SARS-CoV-2 infection (Dangi et al, 2021(Dangi et al, , 2022Fielding et al, 2021;Yewdell et al, 2021). These discoveries suggest that the inclusion of N into a COVID-19 vaccine formulation may be important for the induction of T cell responses, and in addition for the stimulation of non-NAb responses.…”
Section: Discussionmentioning
confidence: 99%